Theoretical Study on a Novel Temperature Breakpoint Cyclic Operation to Enhance Desiccant Packed Bed Performance - Siripan Murathathunyaluk; Prakob Kitchaiya (My University, 2021)
In a conventional desiccant packed bed dehumidification, the adsorption and desorption operations switched at a constant cycle. However, this Conventional Steady Cyclic (CSC) operation was not performed well under disturbances. Therefore, a Temperature Breakpoint Cyclic (TBC) operation is proposed. A numerical model of the desiccant packed bed dehumidification system has been constructed and validated. The model was then used to assess the desiccant packed bed dehumidification performances in term of moisture removal capacity (MRC) and dehumidification coefficient of performance (DCOP) under various cycle times and temperature factors. The calculation results showed that under CSC, larger amounts of energy were required in the desorption operation, while the TBC exhibited higher performances in term of both MRC and DCOP. Notably, at a high regeneration temperature, the MRC of the TBC was 10% higher than the CSC’s; moreover, the DCOP of the TBC was twice higher than the CSC’s. In other words, at high recovery temperature, both operations exhibited comparable capacities while the energy cost was halved under TBC operation.
Keywords: Adsorption and Cooling Systems